2020
DOI: 10.3390/rs12111877
|View full text |Cite
|
Sign up to set email alerts
|

Global Airborne Laser Scanning Data Providers Database (GlobALS)—A New Tool for Monitoring Ecosystems and Biodiversity

Abstract: Protection and recovery of natural resource and biodiversity requires accurate monitoring at multiple scales. Airborne Laser Scanning (ALS) provides high-resolution imagery that is valuable for monitoring structural changes to vegetation, providing a reliable reference for ecological analyses and comparison purposes, especially if used in conjunction with other remote-sensing and field products. However, the potential of ALS data has not been fully exploited, due to limits in data availability and validation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…After a period of intensive research that has shown the irreplaceability of ALS‐derived vegetation structure variables for understanding species–environment relationships, it is now time to make them available to a wider audience which will allow incorporating them as common variables in predictive models. Finding new ways to make ALS data easily accessible is a priority to accelerate ecological research (Assmann et al, 2022; Stereńczak et al, 2020). It would be valuable to have a list of several standardized variables recommended for use in SDM and ecological research, so that scientists or authorities generating ALS‐derived products know which to focus on.…”
Section: Which Vegetation Structure Variables Should Be Provided As S...mentioning
confidence: 99%
“…After a period of intensive research that has shown the irreplaceability of ALS‐derived vegetation structure variables for understanding species–environment relationships, it is now time to make them available to a wider audience which will allow incorporating them as common variables in predictive models. Finding new ways to make ALS data easily accessible is a priority to accelerate ecological research (Assmann et al, 2022; Stereńczak et al, 2020). It would be valuable to have a list of several standardized variables recommended for use in SDM and ecological research, so that scientists or authorities generating ALS‐derived products know which to focus on.…”
Section: Which Vegetation Structure Variables Should Be Provided As S...mentioning
confidence: 99%
“…Second, LiDAR data is critical for mapping the x, y of trees and delineating the tree top position and tree crowns into polygons from which other spectral analyses can be undertaken. Broadly discrete return airborne LiDAR surveys are continuing to expand across urban areas in the United States (Stoker and Miller, 2022) across the globe (Stereńczak et al, 2020). Although repeat time is infrequent (e.g., 5 to 10 years), initial LiDAR surveys provide baseline data on tree location, crown area, and height along with other more complex metrics that can be used in species identification.…”
Section: Future Advancesmentioning
confidence: 99%
“…We therefore recommend that ALS metrics of vertical variability of vegetation should not be restricted to SD and FHD, but also include skewness, kurtosis and CV of vegetation height. Moreover, some authors emphasize that FHD is not designed to describe continuous variables, and hence suggest replacing FHD with Lorenz curves and Gini coefficients (Valbuena et al, 2021). Whether these alternative metrics do indeed provide a better description of the vertical variability of vegetation than FHD needs to be tested with a range of datasets and in different ecosystems, not only in forests.…”
Section: F I G U R Ementioning
confidence: 99%
“…horizontal variability) needs to be aggregated at a coarser resolution (Graham et al, 2019). The time for such assessments is ripe because (1) a large number of country‐wide ALS datasets is now openly accessible (see overviews in Kissling et al, 2022; Moudrý et al, 2023; Stereńczak et al, 2020), (2) user friendly, free and open source software has been developed to calculate a large range of ALS metrics (Meijer et al, 2020; Roussel et al, 2020) and (3) high‐throughput (reproducible and open source) workflows are now available to perform the efficient, scalable, distributed and standardized processing of multi‐terabyte LiDAR point clouds into ALS metrics (Kissling et al, 2022). Until such assessments are performed, proposing a list of 10 ALS metrics may seem premature.…”
Section: Figurementioning
confidence: 99%